Molecular, cellular and functional imaging of atherothrombosis. - Choudhury, R; Fuster, V; Fayad, Z (2004)
Recent years have seen a dramatic expansion in our knowledge of the events of atherogenesis and in the availability of drugs that can retard the progression - and even induce the regression - of this disease process. Our understanding has been advanced considerably by developments in genetics and molecular biology and by the use of genetically modified mouse models that have provided key mechanistic insights. Increasingly sophisticated imaging techniques will capitalize on these advances by bringing forward diagnosis, enhancing disease characterization and providing more precise evaluation of the effects of treatment. In this review, techniques for imaging atherosclerosis and thrombosis will be discussed. Particular attention will be given to magnetic resonance imaging techniques that enable lesion characterization and allow the targeted imaging of cells, molecules and biological processes. Emphasis is given to the potential contribution of magnetic resonance imaging methods to therapeutic monitoring, drug delivery and drug discovery.